Climate Change Communication by a Research Institute: Experiences, Successes, and Challenges from a North European Perspective - Jari Lyytimäki; Nina A. Nygrén; Ulla Ala-Ketola; Sirpa Pellinen; Virpi Ruohomäki; Aino Inkinen (Routledge Taylor & Francis Group, 2022)
Communicating about climate change is challenging not only because of the multidisciplinary and complex nature of the issue itself and multiple policy options related to mitigation and adaptation, but also because of the plenitude of potential communication methods coupled with limited resources for communication. This article explores climate change communication based on experiences from different campaigns by a national level research institution. Lessons learned are discussed in a context of increasing projectification and budget austerity. Possible solutions for enhanced communication include simultaneous use of multiple communication channels, the creation of novel partnerships, focusing on solutions, and the use of peer communication.